1989
DOI: 10.1055/s-2007-1024879
|View full text |Cite
|
Sign up to set email alerts
|

Sports-Related Injuries in Children

Abstract: Within a 3-year period, from 1980 to 1982, 1124 sports injuries of children aged 6-15 years were treated in the Turku University Central Hospital casualty department. Two-thirds (69%) of the injuries were sustained by boys. Sports injuries represented 21% of the diagnoses related to accidents in this age group. Half of the sports accidents occurred during the 4 winter months. Boys were injured most commonly in ice hockey (36%) and football (20%) and girls in skating (18%) and riding (18%). One quarter (26%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 8 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Previous authors have identified a high level of presentation of injury in children involved in cycling [8]. This was apparent in this study, but in addition it highlights the high odds of multiple types and sites of injury in this sport.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Previous authors have identified a high level of presentation of injury in children involved in cycling [8]. This was apparent in this study, but in addition it highlights the high odds of multiple types and sites of injury in this sport.…”
Section: Discussionmentioning
confidence: 46%
“…Previous studies on sport related injuries have largely focused on older children [8,18,22], a combination of adult and paediatric sport injuries [1,14] or included general childhood injuries [3,15]. This present study, however, is the largest and most detailed study of paediatric SRIs presenting to an emergency medical department, conducted in Ireland, and to the best of our knowledge, the second largest study in the worldwide literature [18].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…x Many reports are provided by hospitals and emergency facilities [6][7][8] and as such do not include injuries treated by pediatricians or general practitioners. x To refine the quality of the data and focus on the circumstances of the injury, some researches have looked prospectively at the occurrence of sports injuries within defined populations.…”
mentioning
confidence: 99%